2022
DOI: 10.1002/bsd2.219
|View full text |Cite
|
Sign up to set email alerts
|

The impact of entrepreneurship on the socio‐economic development of regions

Abstract: The relevance of the present article is explained by the need for a detailed study of the influence of medium and small business representatives on the economic indicators of the Republic of Kazakhstan. In this regard, this study is aimed at identifying or covering the development of entrepreneurship theory and establishing methodological approaches that allow assessing the impact of entrepreneurship on the socioeconomic development of regions. The leading method for the researched subject is a systems analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This frame of reference is evidenced in examples such as the search for a circular supply chain (Härri et al, 2023), innovation towards a sustainable industry (Narkhede et al, 2023), the application of this modality in companies with different size (small, medium and large) (Madrid-Guijarro & Duréndez, 2023), and the reformulation of types of company according to their integration to these objectives (Riso et al, 2023). Said transversality is also evidenced in CSR actions, which are visible in the regulation of environmental impact (Panda & Kanti, 2023;Wulansari & Adhariani, 2023), the attention in favor of the surrounding community (Patil & Vhavale, 2022), the influence of companies in the economic development of their regions (Zhakupov et al, 2022), and the participation of the government itself to promote better practices (Hossain et al, 2023). All these proposals arise in a global scenario in which companies with profit-oriented purposes are questioned, and others are raised in which participation oriented towards society and the environment is promoted.…”
Section: The Importance and Challenges Of Sdgs And Csrmentioning
confidence: 99%
“…This frame of reference is evidenced in examples such as the search for a circular supply chain (Härri et al, 2023), innovation towards a sustainable industry (Narkhede et al, 2023), the application of this modality in companies with different size (small, medium and large) (Madrid-Guijarro & Duréndez, 2023), and the reformulation of types of company according to their integration to these objectives (Riso et al, 2023). Said transversality is also evidenced in CSR actions, which are visible in the regulation of environmental impact (Panda & Kanti, 2023;Wulansari & Adhariani, 2023), the attention in favor of the surrounding community (Patil & Vhavale, 2022), the influence of companies in the economic development of their regions (Zhakupov et al, 2022), and the participation of the government itself to promote better practices (Hossain et al, 2023). All these proposals arise in a global scenario in which companies with profit-oriented purposes are questioned, and others are raised in which participation oriented towards society and the environment is promoted.…”
Section: The Importance and Challenges Of Sdgs And Csrmentioning
confidence: 99%
“…However, some studies have concluded that importing digitally offered services positively impacts women's entrepreneurship in European countries (Gaweł and Mi nska-Struzik, 2023). For instance, Zhakupov et al (2023) discussed the components that influence the successful development of the entrepreneurial environment in Kazakhstan. The authors concluded that SMEs focus on importing goods into the country for resale rather than producing them, and they suggested encouraging young entrepreneurs and startups.…”
Section: Institutions and Entrepreneurial Activitiesmentioning
confidence: 99%
“…However, some studies have concluded that importing digitally offered services positively impacts women's entrepreneurship in European countries (Gaweł and Mińska-Struzik, 2023). For instance, Zhakupov et al. (2023) discussed the components that influence the successful development of the entrepreneurial environment in Kazakhstan.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations